Effect of Phosphate Solubilizing Bacteria and Mycorrhizal Fungi on Phenological and Physiological Characteristics of Wheat under Dryland Conditions - Rahim Naseri; Mehrshad Barary; Mohammad Javad Zarea; Kazem Khavazi; Zahra Tahmasebi; Anita Yaghotipoor (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī, 2018)
To study the effect of phosphate solubilizing bacteria (PSB) and mycorrhizal fungi on phonological and physiological traits of wheat, an experiment was carried out in factriol arrangement using randomized complete block design with three replications at the Agriculture and Natural Resources Research Center, Sarableh (Ilam), Iran, during 2013-2014 cropping season. Experiment factors consisted of two dry land wheat cultivars (Cross Sablan and Saji) and fertilizer levels were 1- without application of phosphorous (P), 2- 100% phosphorous application, 3- Pseudomonas putida, 4- Funeliformis mosseae, 5- P. putida + F. mosseae, 6- P. putida + F. mosseae + 50% of phosphorious fertilizer, 7- P. putida + 50% of phosphorious fertilizer and 8- F. mosseae + 50% of phosphorious fertilizer. Results indicated that using chemical and biofertilizer affected 50% days to emergence, stem elongation, flowering, pollination, maturity weight and maturity significantly. Results also showed that using of bio-fertilizer reduced drought stress effects by improving phonological traits of wheat under dry land conditions. The highest LAI, CGR, TDM, RGR and NAR were obtained by Saji cultivar and application of 50% of phosphorious fertilizer + Mycorrhiza fungi, but it effect at late season on CGR, RGR and NAR due to increased shading of plants and leaf falling were negative. The Saji cultivar and 50% of phosphorious fertilizer + F. mosseae because of maximum LAI, CGR and TDM produced higher grain yield under dry land conditions. It can be concluded that Saji cultivar along with F. mosseae may have higher growth indices and seed yield under dryland conditions.